E-stablishing an inclusive society? Technology,social exclusion and UK government policy making - Selwyn, Neil (2002)
In many industralised countries information and communication technology (ICT) is now being seen as a ready means through which governments can address issues of social exclusion. Indeed, in the UK this perspective has been quickly translated into a multi-billion pound policy agenda aimed at using ICT for socially inclusive purpose. Yet, beyond rhetorical concerns over bridging the perceived 'digital divide' and alleviating disparities between the information 'rich' and 'poor', little critical consideration has been given to how technology is being used by governments to achieve socially inclusive aims. This paper therefore examines the UK government's ICT-based social policy drive through official documentation, policy statements and political discourse-considering the 'problems' that it sets out to address, the substance of the policies, and the perceived rationales and benefits for doing so. Having explored the official construction of these policies, the paper then examines how well founded this policy framework is in terms of achieving its stated aims of widening access to ICT and effective facilitating 'social inclusion'. The paper concludes by developing a critical perspective of such ICT policies which reveals deeper economic rationales informing this ostensibly 'social' policy programme. - Reproduced.
Keywords: Communication technology; Electronic governance